INVESTIGANDO INDICADORES DE RESILIÊNCIA EM HABITAÇÃO DE INTERESSE SOCIAL: O CASO DO BAIRRO SHOPPING PARK - Vasconcellos, Paula; Villa, Simone (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Within the environmental and social impacts and rapid urbanization processes, caused by economic, climatic and political changes, the low quality of architecture and urbanism produced, especially in developing countries, increases the level of social vulnerability that reaches millions of people, especially regarding housing access. It is necessary to understand resilience as an adaptive capacity to combat this vulnerable state, improving the built environment and its relationship with the community by reducing/healing small and constant impacts harmful in the long run. In this scenario, a master's research, entitled " COPRODUCING RESILIENCE IN SOCIAL HOUSING: How to assess resilience through collaborative practice?", is structured through the concept of social resilience and coproduction, and its impacts on the built environment, having as a case study a Social Housing Neighbourhood called Shopping Park, in Uberlândia (MG). The Dissertation aims to investigate the neighbourhood resilience indicators, identifying the impacts and qualities that determine such resilience, at the built environment level and in its relationship with its residents. This article presents part of the research focusing on the process of foundation and construction of the evaluation matrix. With the results, we intend to understand the investigative process of identifying social resilience indicators in the built environment.